2021
DOI: 10.1093/ehjci/jeab174
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in left ventricular remodelling in patients with severe aortic valve stenosis

Abstract: Aims  Women with severe aortic stenosis (AS) have better long-term outcome after transcatheter aortic valve implantation (TAVI) but worse survival after surgical aortic valve replacement compared with men. Whether this is related to sex differences in left ventricular (LV) remodelling is unknown. The aim of this study was to examine the sex differences in LV remodelling with multidetector row computed tomography (MDCT) and outcome in patients with severe AS undergoing TAVI between 2007 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[ 51 ] In contrast to echocardiographic studies, Kuneman et al reported more LV concentric remodelling in men with severe AS compared with women, whereas the frequency of the other LV remodelling patterns was similar in both sexes. [ 10 ] Furthermore, there was a significant association between LV concentric hypertrophy and poor survival in men, findings that contrast with the echocardiographic study. [ 46 ] Differences in the type of patients and imaging techniques used to assess LV remodelling may explain the discrepant results of the studies.…”
Section: Ctmentioning
confidence: 82%
See 2 more Smart Citations
“…[ 51 ] In contrast to echocardiographic studies, Kuneman et al reported more LV concentric remodelling in men with severe AS compared with women, whereas the frequency of the other LV remodelling patterns was similar in both sexes. [ 10 ] Furthermore, there was a significant association between LV concentric hypertrophy and poor survival in men, findings that contrast with the echocardiographic study. [ 46 ] Differences in the type of patients and imaging techniques used to assess LV remodelling may explain the discrepant results of the studies.…”
Section: Ctmentioning
confidence: 82%
“…Contrast-enhanced CT can also be used for characterisation of LV remodelling in response to severe AS. [ 10 ] This 3D imaging technique provides high spatial resolution images to assess LV mass and volumes. Furthermore, novel technologies allow the assessment of the extracellular volume as a measure of myocardial fibrosis.…”
Section: Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation may be the sex-speci c myocardial remodeling in AS. Previously, our group examined the impact of sex on LV remodeling before TAVI and reported that the outcome bene ts of women after TAVI were not associated with sex differences in LV remodeling [33]. However, the impact of the potential sex-related differences in LV reverse remodeling after TAVI on outcomes remained unexplored.…”
Section: Sex Differences In Outcomes After Tavi and Association With LV Reverse Remodelingmentioning
confidence: 99%
“…Changes in LV volumes and LV mass index as well as LVEF over time, are displayed in Figure1. At 6 and 12 months after TAVI, both men and women showed a signi cant reduction in LVEDVi (from 48 [39-59] ml/m 2 to 44 [37-55] ml/m 2 at 6 months and to 43[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] ml/m 2 at 12 months after TAVI; and from 39[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] ml/m 2 to 38[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] ml/m 2 at 6 months and to 36 [28-43] ml/m 2 at 12 months, respectively, both p<0.001) and in LVESVi (men: from 22[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ml/m 2 to 20 [16-27] ml/m 2 at 6 months and to 19[15- …”
mentioning
confidence: 99%